2016
DOI: 10.1007/s00404-016-4222-7
|View full text |Cite
|
Sign up to set email alerts
|

New adverse obstetrics outcomes associated with endometriosis: a retrospective cohort study

Abstract: Our results showed for the first time that women with endometriosis are at higher risk of developing ICP and experiencing an induced labor. Further studies are warranted to clarify whether the history of endometriosis might be taken into account in the antenatal care of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(101 citation statements)
references
References 31 publications
6
94
1
Order By: Relevance
“…Preterm delivery. In total, 16 studies were identified investigating the association between endometriosis and ª 2018 Nordic Federation of Societies of Obstetrics and Gynecology, Acta Obstetricia et Gynecologica Scandinavica 97 (2018) 1073-1090 preterm delivery (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The meta-analyses showed that women with endometriosis had a higher odds of preterm delivery (OR 1.47, 95% CI 1.28-1.69) than women without endometriosis (Figure 2a).…”
Section: Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm delivery. In total, 16 studies were identified investigating the association between endometriosis and ª 2018 Nordic Federation of Societies of Obstetrics and Gynecology, Acta Obstetricia et Gynecologica Scandinavica 97 (2018) 1073-1090 preterm delivery (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The meta-analyses showed that women with endometriosis had a higher odds of preterm delivery (OR 1.47, 95% CI 1.28-1.69) than women without endometriosis (Figure 2a).…”
Section: Endometriosismentioning
confidence: 99%
“…Overall, studies on the association between endometriosis and preterm delivery and SGA have pointed in different directions; some reported an increased risk of preterm delivery (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(22)(23)(24) and having an SGA child (9,(14)(15)(16)(17)(18)20,(23)(24)(25), whereas other did not support this (10,(20)(21)(22)25). Regarding adenomyosis, all published studies found an increased risk of preterm delivery (26)(27)(28)(29) and SGA (26)(27)(28), but with considerable differences in the strength of the association.…”
Section: Small For Gestational Agementioning
confidence: 99%
“…In the past 10 years, several studies have reported a correlation between endometriosis and major adverse obstetric outcomes, such as spontaneous late miscarriage 4 , preterm prelabor rupture of the membranes and preterm birth [5][6][7][8][9][10][11] , small-for-gestational age (SGA) 5,10 , hypertension 9 , pre-eclampsia 5,8,11 , gestational diabetes 10 , obstetric hemorrhage (such as abruptio placentae and postpartum bleeding) 5,9,11 and placenta previa [5][6][7]9,12 . However, other studies 12,13 and a systematic review 14 did not confirm completely the increased risk of obstetric complications in women with endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…An increased prevalence of placenta praevia in association with deep endometriotic lesions within the posterior pelvic compartment was also reported in a subsequent cohort [17.1% (7/41) in women with ≥2 cm nodules versus 0.3% (1/300) in women without a diagnosis of endometriosis (OR, 61.6; 95% CI, 7.4–515.5)] . One further series, however, did not find a difference between deep and more superficial endometriosis in the rate of placenta praevia . Several pathogenic hypotheses have been formulated regarding the mechanisms underlying a possible association between deep endometriosis and placenta praevia …”
Section: The Effect Of Severe Forms Of Endometriosis and Deep Lesionsmentioning
confidence: 81%
“…6 One further series, however, did not find a difference between deep and more superficial endometriosis in the rate of placenta praevia. 7 Several pathogenic hypotheses have been formulated regarding the mechanisms underlying a possible association between deep endometriosis and placenta praevia. 1,5,6 The additional effect of IVF, twinning, and blastocyst transfer on the incidence of placenta praevia An almost four-fold increase in risk of placenta praevia was observed in singleton pregnancies after ART compared with those conceived naturally (RR, 3.7; 95% CI, 2.7-5.2).…”
Section: The Association Between Endometriosis and Placenta Praeviamentioning
confidence: 99%